Stakeholders’ Activities for Greening Supply Chains: The Case of Rail Noise Reduction - Joanna MIKLINSKA (Communications of International Proceedings, 2022)
Noise is a problem in the modern world, affecting people living in cities, urban areas and other places. It reaches people from many sources, reducing their quality of life and even leading to disease. One significant emitter of noise today is transport activity. Within the different modes of transport, the problem occurs with varying intensity. This article addresses this issue in relation to rail transport. This mode of transport, although recognised as an environmentally friendly and sustainable solution, is a significant source of noise emissions to the environment. Given the many advantages of rail, including in terms of low negative externalities other than noise, there is a contemporary trend to move freight 'from road to rail' and to use this mode of transport in green supply chains. In order to reap the full benefits from this transport mode, the problem of rail noise is undoubtedly one that needs to be solved. Among experts and various stakeholders directly involved in the rail sector, this issue has been addressed for a long time. In order to reduce railway noise, international regulatory measures are being implemented and numerous technical solutions are being introduced. At a time when also in Poland, in accordance with the concept of sustainable development of transport, the role of rail transport is sought to be strengthened, it is important to examine how the problem of rail noise is perceived and solved here. Hence, the aim of this article is to present rail noise reduction solutions undertaken for the greening of supply chains by various stakeholders associated with the rail market in Poland, against the background of regulations and trends that exist in this respect internationally. In order to achieve the main objective of the article, the author analysed reference literature and reports on trends in supply chains, the greening of supply chains and environmental and rail noise issues in an international perspective. The author also analysed legislation, statistical data and recently published reports, as well as source information on the rail market in Poland and rail noise from the Office of Railway Transport and PKP PLK - the largest manager of liner rail infrastructure in Poland.
Keywords: Environmental Noise; Rail Noise; Rail transport; Green Supply Chain